NILAI PENDIDIKAN KARAKTER PADA TEKS CERITA FANTASI - Rosary Iriany; Rusman Latif (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Value of Character Education in Fantasy Story Text. This study aims to describe the form of the 2013 Curriculum's Class VII Indonesian Language Books for SMP/MTs. This research is a type of qualitative research. The research design is a qualitative, descriptive research design. The data in this study are words, phrases, sentences, and paragraphs that contain educational character values in three types of literary texts, namely fantasy story texts. Indonesian books for class VII SMP  and MTs published by the Ministry of Education and Culture Curriculum 2013 Revised Edition 2017 were used as data sources in this study. The results showed that there are five values in the form of character education values in fantasy story texts, with twenty-one sub-values. Religious values (sub-values of faith, sincerity, and friendship), nationalist values (sub-values of environmental protection, willingness to sacrifice, love of the motherland, discipline, and cultural appreciation), independent values (sub-values of work ethic, courage, fighting power, and achievement), mutual cooperation values (sub-values of solidarity, cooperation, empathy, deliberation to reach a consensus), and cultural appreciation are all manifestations of these character education values.